The moving finger - Christie, Agatha, 1890-1976. (New York : Berkley Books, 1984)
Anonymous letters are sent to almost everyone in the quiet village of Lymstock. After suicide and murder occur, the vicar's wife calls in her own expert--Miss Jane Marple.
"A Miss Marple mystery"--Cover.
Young Adult
Keywords: Marple, Jane (Fictitious character) -- Fiction; Murder -- Fiction; Suicide -- Fiction; Homicide -- Fiction; Marple, Jane (Fictional character) -- Fiction; Mystery fiction; Suicide -- Fiction; England -- Fiction; England -- Fiction; Detective and mystery stories